Caught Looking: Feminism, Pornography and Censorship Fact ... - Davidson, Carol Margaret (Canadian Woman Studies/les cahiers de la femme, 1994)
Dirty Looks: Women Pornography and Power; The Jaguar and the Anteater: Pornography and the Modern World; Making Violence Sexy: Feminist Views on Pornography; Pornography, Women, Violence and Civil Liberties: A Radical New View; Pornography and Feminism: The Case Against Censorship; Sex Exposed: Sexuality and the Pornography Debate